Heterotopic pancreas causing jejunal obstruction in a neonate - Hiroshi Hamada; Yoshinori Hamada; Tatsuma Sakaguchi; Takashi Doi (Elsevier, 2019)
Heterotopic pancreas (HP) is a rare entity. HP is rarely diagnosed during the neonatal period, and only a few neonatal cases of HP causing gastrointestinal obstruction have been reported. We herein describe a rare case of HP causing jejunal obstruction in the early neonatal period and discuss the association of an inflammatory process in this case. Keywords: Heterotopic pancreas, Neonate, Gastrointestinal obstruction, Jejunum